MOS spectroscopy of protocluster candidate galaxies at z = 6.5. Issue 3 (16th August 2019) - Calvi, R; Rodríguez Espinosa, J M; Mas-Hesse, J M; Chanchaiworawit, K; Guzman, R; Salvador-Solé, E; Gallego, J; Herrero, A; Manrique, A; Marín Franch, A
ABSTRACT: The epoch corresponding to a redshift of z ∼ 6.5 is close to full re-ionization of the Universe, and early enough to provide an intriguing environment to observe the early stage of large-scale structure formation. It is also an epoch that can be used to verify the abundance of a large population of low luminosity star-forming galaxies that are deemed responsible for cosmic re-ionization. Here, we present the results of follow-up multi-object spectroscopy using OSIRIS at Gran Telescopio Canarias of 16 Ly α emitter (LAE) candidates discovered in the Subaru/XMM Newton Deep Survey. We have securely confirmed 10 LAEs with sufficient signal-to-noise ratio of the Ly α emission line. The inferred star formation rates of the confirmed LAEs are on the low side, within the range 0.9–4.7 M⊙ yr −1 . However, they show relatively high Ly α rest frame equivalent widths. Finally we have shown that the mechanical energy released by the star formation episodes in these galaxies is enough to create holes in the neutral hydrogen medium such that Lyman continuum photons can escape to the intergalactic medium, thus contributing to the re-ionization of the Universe.